The Epidemiology of Depression and Diabetes Distress in Type 2 Diabetes in Kuwait - Ebaa Al-Ozairi; Abdulla Al Ozairi; Clare Blythe; Etab Taghadom; Khalida Ismail (Journal of Diabetes Research)
This study is aimed at describing the prevalence of and risk factors for depression and diabetes distress in people with type 2 diabetes and whether depression and distress are independently associated with worse biomedical outcomes. The study was of cross-sectional design. The setting was the Dasman Diabetes Institute, Kuwait. The Patient Health Questionnaire-9 (PHQ-9) was used to measure the prevalence of depression, defined as a score≥10 (depression caseness). The Problem Areas in Diabetes (PAID) was used to measure diabetes-related distress. Data on biomedical outcomes, lifestyle factors, and sociodemographic information were collected. The prevalence of depression and diabetes distress caseness was 29% and 14%, respectively. Depression caseness patients were more likely to be female (60%; p=0.001), have Kuwaiti nationality (68%, p=0.121), were on insulin (67%, p=0.001), have higher body mass index (p=0.047), were less physically active (78%; p=0.034), have a higher PAID score (p<0.001), and have hypertension (74%, p=0.047). After adjustment of sociodemographics (age, gender, and marital status) and body mass index, the prevalence of depression was associated with higher HbA1c (B=0.04, 95% confidence interval 0.01 to 0.60), while diabetes distress had a weak association with HbA1c (B=0.13, 95% confidence interval 0.04 to 0.22). In conclusion, people with type 2 diabetes in Kuwait have a high prevalence of depression but lower diabetes distress and this was associated with worse glycaemic control.